Pelaksanaan Pengawasan dalam Kegiatan Tahsin dan Tahfidz di Pondok Pesantren Madinatul Qur’an Desa Betung Kabupaten Ogan Ilir - Siti Aisyah; Padli Padli; Ibnu Rozali (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study is entitled “The Implementation of Supervision in Tahsin and Tahfidz Activities at Madinatul Qur’an Islamic Boarding School, Betung Village, Ogan Ilir Regency.” The study aims to analyze the implementation of supervision in tahsin and tahfidz activities at Madinatul Qur’an Islamic Boarding School, as well as to identify the supporting and inhibiting factors in the supervision process of tahsin and tahfidz activities at Madinatul Qur’an Islamic Boarding School, Betung Village, Ogan Ilir Regency. This research is a qualitative study using a descriptive approach. Data collection techniques include observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and conclusion drawing. Data validity is tested through technique triangulation and source triangulation. The results of the study indicate that supervision in tahsin and tahfidz activities at this Islamic boarding school is carried out routinely and in a structured manner through direct guidance from the teachers. The supervision process begins with the formulation of Qur’anic reading and memorization standards, which are collaboratively developed by the teachers, approved by the boarding school leadership, and periodically adjusted to meet the needs of the students. The implementation is evaluated regularly to assess students’ achievements based on the established standards. Any deviations are followed up with intensive guidance and individual mentoring. Supporting factors for the success of supervision include teacher competence, a disciplined control system, and a conducive boarding school environment. Meanwhile, the obstacles identified include the low level of discipline among some students and their tendency to request permission to be absent for various reasons. Nevertheless, continuous guidance and supervision are consistently carried out to ensure improvement and the achievement of optimal targets. Thus, the implementation of supervision in tahsin and tahfidz activities at Madinatul Qur’an Islamic Boarding School has been conducted effectively. It is expected that in the future, the quality of these activities can continue to be improved in order to provide greater benefits for the development of students and the Islamic boarding school institution